SISTEM PENDUKUNG KEPUTUSAN SELEKSI PELANGGAN TERBAIK INDIHOME CUSTOMER GATHERING MENGGUNAKAN METODE WP (STUDI KASUS: PT. TELKOM WITEL PAPUA) - Hasan, Patmawati; Heru Sutejo (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
This study aims to conduct customer selection and determine the ranking of the best customers to receive rewards and invitations as guests in the annual Indihome Customer Gathering event at PT. Telkom Indonesia Witel Papua. Data from 13,038 Indihome customers in Jayapura in August 2021 were processed, with 8 selected as samples. The Rapid Application Development (RAD) method was employed for system development, comprising four phases: Requirements Planning, User Design, Construction, and Cutover. The system design utilized the Unified Modeling Language (UML), incorporating Use Case, Class, and Sequence Diagrams. The Decision Support System was tested on 8 customer samples using Blackbox testing, comparing manual and system testing for validation. The research result is a decision support system for customer selection and ranking based on the Weighted Product Method. Among the 8 customer samples, the top 3 rankings were identified. Invitations were sent via email, with Bimbo Thalib ranking first with a score of 0.1929, Alfa Rieuwpassa second with 0.173, and Minggu Roben 0168 third. The system is expected to aid employees in customer selection, invite the best customers, and enhance event effectiveness.